(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
In this article, the author provides an analysis of the specifics and features of the current state of the personnel reserve mechanism in the field of state and municipal service. The author gives a description of the modern features of the formation of a personnel reserve on the basis of which aspects of modernization changes in the state reserve of managerial personnel are proposed.